Predation on sea turtles by jaguars in the Mexican Caribbean - Rosales-Hernández, Víctor A.; Cruz-Romo, Lizardo; Contreras-Moreno, Fernando M.; Petrone, Sandra; Jesús-Espinosa, Daniel (Therya Notes, 2022)
Jaguars are opportunistic carnivores whose diet mainly depends on prey availability. Jaguar predation on sea turtles has not been sufficiently documented in México. In this study, we recorded the predation of loggerhead (Caretta caretta) and green (Chelonia mydas) sea turtles by jaguar (Panthera onca) in Mahahual, Quintana Roo, México. From May to August 2021, 10 camera-trap stations were set on a nesting beach. Meanwhile, daytime and nighttime tours were conducted along the beach to detect turtles nesting on the site, as well as carcasses with evidence of predation. With a sampling effort of 600 camera trap nights, we obtained 10 independent jaguar predation events and 3 photo events confirming jaguar predation on sea turtles. Jaguar predation on sea turtles has been documented on Costa Rican beaches, but rarely in México. This report contributes to improving our understanding of the diet of the jaguar in coastal areas and the relationship between this feline species and sea turtles in México.